Relationship Of Obesity, Anxiety Level And Sleep Quality In Pregnant Women With Preeclamsia In Rsud Dr. Hm Rabain Muara Enim 2021 - Hilaliah; Ahmad Arif; Helni Anggraini (Science Midwifery, 2022)
Preeclampsia was defined as new-onset gestational hypertension with a systolic blood pressure greater than or 140 mmHg and/or a diastolic blood pressure of 90 mmHg associated with new onset of at least one proteinuria, maternal organ dysfunction or uteroplacental dysfunction at or after 20 weeks ' gestation. This study aims to determine the relationship between obesity, anxiety levels and sleep quality, in pregnant women simultaneously with the incidence of preeclampsia in RSUD Dr.H.M. Rabain Muara Enim in 2021. The method used in this study is an analytical observational study with a cross sectional design or approach. The population in this study were all pregnant women with gestational age more than or 20 weeks, with a total sample of 46 people. Data were collected, processed and analyzed using univariate and bivariate analysis. The sampling technique was using purposive sampling. The statistical test used was the chi square test. Through data analysis, it was found that there was a relationship between obesity in pregnant women and the incidence of preeclampsia with p value = 0.001 < = 0.05, there was no relationship between anxiety levels of pregnant women and the incidence of preeclampsia with p value = 0.191 > = 0.05, and there is a relationship between the quality of sleep of pregnant women with the incidence of preeclampsia with p value = 0.031 < = 0.05. The results of this study are expected to be used as input for improving the quality of services for pregnant women so that they can reduce the incidence of preeclampsia and at the same time reduce maternal mortality.